2016
DOI: 10.1111/1365-2435.12621
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits as predictors of vital rates across the life cycle of tropical trees

Abstract: Summary 1.The 'functional traits' of species have been heralded as promising predictors for species' demographic rates and life history. Multiple studies have linked plant species' demographic rates to commonly measured traits. However, predictive power is usually low -raising questions about the practical usefulness of traits -and analyses have been limited to size-independent univariate approaches restricted to a particular life stage. 2. Here we directly evaluated the predictive power of multiple traits sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
252
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 182 publications
(267 citation statements)
references
References 71 publications
(183 reference statements)
14
252
1
Order By: Relevance
“…The negative relationship between Relative Height Increment and seed mass recorded in our experiment corroborate several other studies using different species and environments (Baraloto et al 2005;Larson et al 2015;Visser et al 2016) including in the Brazilian Cerrado (Pereira et al 2013). Turnbull et al (2012) suggest that this relationship can be related with the strategy of growth rates among species (the fast-slow continuum hypothesis).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The negative relationship between Relative Height Increment and seed mass recorded in our experiment corroborate several other studies using different species and environments (Baraloto et al 2005;Larson et al 2015;Visser et al 2016) including in the Brazilian Cerrado (Pereira et al 2013). Turnbull et al (2012) suggest that this relationship can be related with the strategy of growth rates among species (the fast-slow continuum hypothesis).…”
Section: Discussionsupporting
confidence: 91%
“…The persistence of the positive effects of seed mass on survival after the stage of seedlings suggests that other correlated functional attributes can be involved in the mechanisms of this relationship (Baraloto et al 2005;Muller-Landau 2010;Laughlin 2014;Visser et al 2016). It is possible that functional traits studies beyond seed mass could explain with more accuracy questions regarding the recruitment and establishment of species on degraded areas, then improving ecological restoration projects (Sandel et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…j (25) (26) (27) the estimation of effect sizes, especially in cases where multiple variables influence the response variable (Grueber et al 2011). Our normalized traits were only weakly correlated (r 2 SM,WD p 0:026; r 2 SM,Dmax p 0:021; r 2 WD,Dmax p 0:0019), and the statistical approach was also vigorously tested by Visser et al (2016a), who, using the same vital rates and trait data, found no issues with nonlinearity, heteroscedasticity, nature of the random effect structure, and lack of random slopesissues that can potentially impact effect sizes and robustness of conclusions. Parameters were averaged over all models, using the zero method.…”
Section: Statistical Fitting Of Vital Rate Functionsmentioning
confidence: 99%
“…We begin by explaining the structure of the composite IPM and vital rate functions. The vital rate functions incorporate three functional traits (seed mass, wood density, and adult stature; see, e.g., Visser et al 2016a) and breeding system. Second, we explain our statistical approach for fitting the vital rates through model averaging and provide an overview of the study site and data used.…”
Section: Model Frameworkmentioning
confidence: 99%
See 1 more Smart Citation